Denoising of iodine-131 images using a median filter. Issue 4 (April 2019) - Pandey, Anil K.; Sharma, Akshima; Sharma, Param D.; Saroha, Kartik; Parida, Girish K.; Bal, Chandra S.; Kumar, Rakesh
Abstract : Objective: An iodine-131 ( 131 I) image visually appears to be contaminated with impulse noise. The two-dimensional median filter removes noise without sacrificing the edge information. Its performance depends on the shape and size of the mask. In this study, we have compared the performance of a plus-shape and a square-shape median filter for 131 I whole-body images and found the filter with optimum parameter that improves 131 I image quality acceptable to nuclear medicine physicians. Materials and methods: A total of 150 whole-body 131 I images were exported in DICOM format. These images were converted into PNG format and processed with a plus-shape and a square-shape median filter, with each shape mask having sizes of 3, 5, 7, and 9 pixels. The quality of the processed images was assessed by visual assessment by two nuclear medicine physicians and also quantitatively by evaluating metrics: mutual information, mean square error, peak signal-to-noise ratio, and difference entropy. Nuclear medicine physicians assigned a score to each image on the scale 1 (lowest) to 5 (highest) for image quality on the basis of the noise removal, smoothness, and edge information available in the image. Student's t -test was carried out to find the significant difference in the image quality ( α =0.05) between the processed images with square-shape and cross-shape mask with the same pixel size. All experiments including statistical analysis were conducted using R installed on a personal computer. Results: Both median filters improved the image quality of 131 I images. The plus-shape median filter was found to show better performance in comparison with the square-shape median filter ( P <0.001). The plus-shape median filter with a mask size of 7 pixels was found to be optimum for the processing of whole-body 131 I images. Conclusion: The plus-shape median filter with a mask size of 7 pixels can be used to process whole-body 131 I scintigraphic images without loss of clinical information.